Novel bioresorbable phosphate glass fiber textile composites for medical applications - Zhu, Chenkai; Ahmed, Ifty; Parsons, Andrew J.; Wang, Yunqi; Tan, Chao; Liu, Jingsong; Rudd, Chris D.; Liu, Xiaoling (Wiley, 2018)
A manual bench-top inkle-type loom was designed to enable hand woven textiles. These PGF textiles, along with unidirectional (UD) fiber mats made from the same batch of yarns, were utilized to manufacture fully resorbable textile composites (T-C), unidirectional aligned fiber composites (UD-C) and 0°/90° lay-up UD fiber reinforced composites (0/90-C). The fiber volume fraction in the composites was set at ~20%. Retention of flexural properties and mass loss of the composites were evaluated during degradation in phosphate buffered saline (PBS) at 37 °C for 28 days. The higher flexural strength and modulus values observed for the T-C when compared to 0/90-C were attributed to the textile weaving resulting in a biased fabric with a higher density of fibers in the warp direction. After 28 days immersion in PBS ~20% flexural strength and ~25% flexural modulus values for the UD-C, T-C and 0/90-C composites were still prevalent.